Small Antimicrobial Resistance Plasmids in Livestock-Associated Methicillin-Resistant Staphylococcus aureus CC398 - Feßler, Andrea; Kadlec, Kristina; Wang, Yang; Zhang, Wan-Jiang; Wu, Congming; Shen, Jianzhong; Schwarz, Stefan (Frontiers in Microbiology, 2018)
LA-MRSA isolates of the clonal complex 398 are often resistant to a number of antimicrobial agents. Studies on the genetic basis of antimicrobial resistance in these bacteria identified SCCmec cassettes, various transposons and plasmids of different sizes that harbor antimicrobial resistance genes. While large plasmids that carry multiple antimicrobial resistance genes – occasionally together with heavy metal resistance genes and/or virulence genes – are frequently seen in LA-MRSA ST398, certain resistance genes are also associated with small plasmids of up to 15 kb in size. These small resistance plasmids usually carry only one, but in rare cases also two or three antimicrobial resistance genes. In the current review, we focus on small plasmids that carry the macrolide-lincosamide-streptogramin B resistance genes erm(C) or erm(T), the lincosamide resistance gene lnu(A), the pleuromutilin-lincosamide-streptogramin A resistance genes vga(A) or vga(C), the spectinomycin resistance gene spd, the apramycin resistance gene apmA, or the trimethoprim resistance gene dfrK. The detailed analysis of the structure of these plasmids allows comparisons with similar plasmids found in other staphylococci and underlines in many cases an exchange of such plasmids between LA-MRSA ST398 and other staphylococci including also coagulase-negative staphylococci.